2023
DOI: 10.1096/fj.202300004rrrr
|View full text |Cite
|
Sign up to set email alerts
|

UFMylation of HRD1 regulates endoplasmic reticulum homeostasis

Hui Luo,
Qi‐Bin Jiao,
Chuan‐Bin Shen
et al.

Abstract: Ubiquitin fold modifier 1 is a small ubiquitin‐like protein modifier that is essential for embryonic development of metazoans. Although UFMylation has been connected to endoplasmic reticulum homeostasis, the underlying mechanisms and the relevant cellular targets are largely unknown. Here, we show that HRD1, a ubiquitin ligase of ER‐associated protein degradation (ERAD), is a novel substrate of UFM1 conjugation. HRD1 interacts with UFMylation components UFL1 and DDRGK1 and is UFMylated at Lys610 residue. In UF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Similar to other ubiquitin-like proteins, UFMylation in uences the stability or subcellular localization of substrate proteins (25)(26)(27)(32)(33)(34). Our study revealed that UFMylation impacted the localization of Eg5, without altering its protein stability.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Similar to other ubiquitin-like proteins, UFMylation in uences the stability or subcellular localization of substrate proteins (25)(26)(27)(32)(33)(34). Our study revealed that UFMylation impacted the localization of Eg5, without altering its protein stability.…”
Section: Discussionmentioning
confidence: 63%
“…Research into these substrates has revealed a broad spectrum of functions associated with this modi cation. For example, UFMylation of RPL26, RPN1, CYB5R3, and HRD1 maintains the ER proteins during ER stress (31,34,(36)(37)(38). UFMylation regulates tumorigenesis through ASC1, SLC7A11, and PD-L1 (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ufmylation is implicated in human diseases, such as hematopoietic diseases ( 16 18 ), heart diseases ( 19 ), diabetes ( 20 ), intestinal exocrine diseases ( 21 ), neuronal diseases ( 22 25 ), and cancer ( 9 , 12 ). At the cellular level, ufmylation regulates endoplasmic reticulum (ER) stress ( 11 , 26 , 27 ), ER-phagy ( 6 , 28 , 29 ), ribosome- and translocation-associated quality control ( 14 , 30 33 ), genomic integrity ( 8 , 15 ), and cell development and death ( 15 , 34 36 ). However, virtually nothing is known about its functions and regulation in cellular protein trafficking.…”
Section: Introductionmentioning
confidence: 99%